Students’ and parents’ attitude towards the SEE English test - Dawadi, Saraswati (Journal of NELTA, 2019)
This paper reports on a study that explored students’ and their parents’ attitudes towards the fairness and accuracy of the Secondary Education Examination (SEE)English test- a high stakes test in the Nepalese context. It is most probably the first empirical study that has extensively explored this area. The data generated through a longitudinal survey among 247 SEE candidates and semi-structured interviews with six students and their parents in both the pre-test and post-test contexts indicates that students had mostly positive attitudes towards the test fairness and its accuracy in the pre-test context but mostly negative attitudes in the post-test context. However, parents had mostly negative attitudes towards the test in both contexts. Both students and their parents raised questions regarding the accuracy and fairness of the listening and speaking test in the post-test context. Having collected both the qualitative and quantitative data, this study has gained a comprehensive picture of the complexity of the test impacts within the Nepalese educational context, as perceived by students and their parents. The implications of the study have also been highlighted.